2017
DOI: 10.1111/hequ.12134
|View full text |Cite
|
Sign up to set email alerts
|

The PhD conundrum in South African academia

Abstract: South African universities need more academics with PhDs, from historically disadvantaged population groups in particular, but they face a conundrum. In order to have more staff with PhDs, they need to produce more PhD graduates. But in order to produce more PhD graduates, they need more staff with PhDs to supervise. This article explores this conundrum by comparing academic qualifications with national policies and targets, by developing a quantitative profile of staff without PhDs and describing government a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Moreover, the differences in PhD students' success found across the program clusters and the modes of study may raise the necessary enquiry and understanding to the causes of the differences in success and hence allow the university stakeholders to design appropriate strategies to improve PhD success per specific domain. Similar findings to this study have been reported in other countries, such as South Africa, USA, and Australia, and, therefore, they are not unique to Kenya (Bair & Haworth, 2004;Breier & Herman, 2017;Cloete et al, 2015;Council of Graduate Schools, 2009;Gittings et al, 2018). In addition, this study paves way for more research on PhD education in developing countries and especially in Kenya.…”
Section: Implications Of the Studysupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the differences in PhD students' success found across the program clusters and the modes of study may raise the necessary enquiry and understanding to the causes of the differences in success and hence allow the university stakeholders to design appropriate strategies to improve PhD success per specific domain. Similar findings to this study have been reported in other countries, such as South Africa, USA, and Australia, and, therefore, they are not unique to Kenya (Bair & Haworth, 2004;Breier & Herman, 2017;Cloete et al, 2015;Council of Graduate Schools, 2009;Gittings et al, 2018). In addition, this study paves way for more research on PhD education in developing countries and especially in Kenya.…”
Section: Implications Of the Studysupporting
confidence: 89%
“…However, the PhD graduates supply presents a gloomy picture as Kenyan universities graduated a total of 1,203 PhDs in four years; 2012-2015, an average of 300 per year (CUE, 2016). For comparison, South Africa graduated 1,878 (in 2012), 2,051 (in 2013) and, 2,258 (in 2014) PhDs respectively (Breier & Herman, 2017;Cloete, Mouton, & Sheppard, 2015). This mismatch of the economy's demand and supply of PhD holders presents a great challenge to planners and policy makers in the Kenyan university sub-sector.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the USA's situation (Johnson, 2017), in South Africa, women outnumber men as holders of bachelor's degrees and PhDs (Breier & Herman, 2017). There are also more women at entry level in the academy's junior ranks and support services.…”
Section: Women Academics In South African Universitiesmentioning
confidence: 90%
“…In Africa, and in other developing countries, the argument is made that there is an urgent need for doctoral graduates to take up academic posts to compensate for the relatively low numbers of academic staff with doctoral qualifications. 8 For example, only 43% of all permanent academics in South African universities had doctorate degrees in 2014 19 , limiting the capacity of the system to supervise future doctoral candidates. Jørgensen 20 found that 33% of staff had a doctorate in 28 sampled institutions in Southern Africa in 2012, compared with 31% of staff in 29 institutions in Latin America and 49% of staff in 28 institutions in East Asia.…”
Section: Reproduction and Developmentmentioning
confidence: 99%